Turning climate risk into joint action: Reflections from the Montreal Climate Security Summit - Pacillo, Grazia; Corvaro, Francesco (2025)
On 8 to 9 October 2025, CGIAR Climate Security joined military leaders, policymakers, researchers, and industry partners in Montreal for the 4th Climate Security Summit organized by NATO CCASCOE and the CDA Institute. The summit’s purpose was to strengthen military adaptation to climate risks and turn cross‑sector dialogue into operational solutions. Plenaries, roundtables, and workshops created an honest space to compare notes on what is changing, what is already breaking, and what we can do together.